Thermal, structural, mechanical and 1.8 μm luminescence properties of the thulium doped Pb-K-Al-Na glasses for optical fiber amplifiers - Basavapoornima, Ch.; Maheswari, T.; Chalicheemalapalli Jayasankar, Deviprasad; Kesavulu, C.R.; Tröster, Thomas; Jayasankar, C.K. (Journal of Non-Crystalline Solids)

Microscopic modeling of the optical properties of semiconductor nanostructures - Thränhardt, A.; Meier, Torsten; Reichelt, Matthias; Schlichenmaier, C.; Pasenow, B.; Kuznetsova, I.; Becker, S.; Stroucken, T.; Hader, J.; Zakharian, A.R.; Moloney, J.V.; Chow, W.W.; et al. (Journal of Non-Crystalline Solids)
A brief overview of a consistent microscopic approach to model the optical and electronic properties of semiconductor nanostructures is presented. Coupled semiconductor Bloch and Maxwell equations are used to investigate the performance of semiconductor microcavity structures, photonic band gap systems, and lasers. The predictive potential of the microscopic theory is demonstrated for several examples of practical importance. Optical gain and output characteristics are computed for modern vertical external cavity surface emitting laser structures. It is shown how design flexibilities can be used to optimize the device performance. Nanostructures are proposed where semiconductor quantum wells are embedded in one-dimensional photonic crystals. For field modes spectrally below the photonic band edge it is shown that the optical gain and absorption can be enhanced by more than one order of magnitude over the value of the homogeneous medium. The increased gain can be used for laser action by placing quantum wells and a suitably designed photonic crystal structure inside a microcavity.

Influence of additives and post-synthesis treatment on the structural properties of sol–gel prepared alumina-doped zirconia studied by EXAFS-spectroscopy and X-ray diffraction - Feth, Martin P.; Bauer, Matthias; Kickelbick, Guido; Metelkina, Olga; Schubert, Ulrich; Bertagnolli, Helmut (Journal of Non-Crystalline Solids)
Keywords: Materials Chemistry; Condensed Matter Physics; Ceramics and Composites; Electronic; Optical and Magnetic Materials